Meteorological Observations at Syowa Station in 1992 by the 33rd Japanese Antarctic Research Expedition - Kazumasa MATSUHARA; Yoshitomo KOJO; Takayuki KISHI; Hiroshi IGARASHI; Keishiro HIGASHIJIMA (National Institute of Polar Research, 1995)
This paper describes the results of meteorological observations carried out by the Meteorological Observation Team of the 33rd Japanese Antarctic Research Expedition (JARE-33) from 1 February 1992 to 31 January 1993 at Syowa Station. The observations, instruments and statistics at Syowa Station were the same as those of the JARE-32 observation team. The principal characteristics in the period of JARE-33 are as follows : 1) Blizzards were encountered twenty-eight times spanning sixty days, both of which are normal. However, two blizzards continued over one hundred hours. 2) In most of the period of the expedition, it was cloudy and windy. Annual mean wind speed was 7.1m/s, mean vapor pressure was 2.4hPa, and mean cloud amount was 7.5. All of these values were maximum records. 3) The Antarctic ozone hole was observed for four successive years. The lowest value of daily total ozone amount was 140m atm-cm on 4 October and the lowest of monthly mean of that was 164m atm-cm in October. Both were the lowest values in the historical record.